Analisis Keamanan Seed Phrase pada Wallet Cryptocurrency Menggunakan Brute Force - I Kadek Adi Sentana; I Gusti Ngurah Anom Cahyadi Putra (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2025)
Cryptocurrency wallets serve as digital repositories for securing various digital assets. The security of these wallets is often bolstered by the utilization of seed phrases, which act as a primary means of access and recovery. This research delves into the examination of wallet security, specifically focusing on assessing the resilience against brute force attacks. Brute force methods entail systematically attempting numerous combinations to crack the seed phrase and gain unauthorized access to the wallet contents. Through meticulous experimentation and analysis, this study aims to provide insights into the effectiveness of seed phrase-based security mechanisms in thwarting brute force intrusion attempts. By evaluating different wallet implementations and their susceptibility to brute force attacks, this research contributes to enhancing the robustness of cryptocurrency wallet security measures